The Transactions Demand for Money and Technological Change - Lieberman, Charles (The Review of Economics and Statistics, 1977)
THE critical nature of the demand for money in macroeconomic analysis has generated a considerable amount of theoretical and empirical research, although much controversy remains. The conventional theoretical frameworks have resulted in two basic money demand models: one an asset demand model and the other a transactions demand model. For the most part, empirical evidence has tended to favor the asset demand formulation.' This paper will report evidence that strongly suggests that the previous empirical studies of the transactions demand for money were misspecified, and that as a result, the conclusions drawn do not usefully discriminate between the asset and transactions theories. The misspecifications are twofold. First, either GNP or NNP has typically been used as a proxy for transactions although there are strong a priori reasons to believe that neither is an adequate measure of transactions.2 Second, as many authors have recognized, technological change could affect the demand for money and regression estimates might be biased if structural changes due to technological innovations are not taken into account. Even so, researchers have dismissed technological change from their studies, typically relegating their observations to footnotes. In this paper, debits to demand deposit accounts (adjusted for currency transactions) are used to replace income as the measure of transactions, and time, which provides a crude estimate of the mean rate of technological change over the sample period, is incorporated into both the theoretical and empirical model. The results demonstrate that the transactions theory of money demand outperforms the asset demand formulation, contrary to much of the currently available empirical evidence. This study also suggests that technological change reduces money demand, ceteeris paribus. by about 1.5% to 2.5% per year. In addition, other issues such as the speed of adjustment to changes in the desired level of money balances and economies of scale in holding money are also addressed. The empirical findings suggest that at least 75%, and as much as 100%, of the gap between desired and actual money holding is closed within one year and that there are substantial economies of scale in holding money, as suggested by monetary theory.